2006
DOI: 10.1093/geront/46.6.726
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Professionally Conducted Cultural Programs on the Physical Health, Mental Health, and Social Functioning of Older Adults

Abstract: The positive impact of participatory art programs for older adults in this study on overall health, doctor visits, medication use, falls, loneliness, morale, and activities reflects important health promotion and prevention effects and a reduction of risk factors driving the need for long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
296
1
23

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(331 citation statements)
references
References 27 publications
11
296
1
23
Order By: Relevance
“…In one study, for example, older adults who participated in a short-term theatre training programme showed significant improvements on measures of cognitive performance and psychological well-being (Staricoff 2004). Cohen et al (2006) found that older people with mood disorders who engaged in choral participation, in contrast with a comparison group who undertook different activities, reported improved general health and morale, reduced loneliness, fewer visits to doctors, a reduction in the number of over-the-counter medications taken. A recent study of singing with older people living with dementia showed improved focus and lucidity after sessions (Davidson and Almeida 2014).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In one study, for example, older adults who participated in a short-term theatre training programme showed significant improvements on measures of cognitive performance and psychological well-being (Staricoff 2004). Cohen et al (2006) found that older people with mood disorders who engaged in choral participation, in contrast with a comparison group who undertook different activities, reported improved general health and morale, reduced loneliness, fewer visits to doctors, a reduction in the number of over-the-counter medications taken. A recent study of singing with older people living with dementia showed improved focus and lucidity after sessions (Davidson and Almeida 2014).…”
Section: Literature Reviewmentioning
confidence: 96%
“…A third theoretical influence has followed from the work of Cohen et al (2006) and their research with older adults attending professionally conducted cultural programmes, which has led to a better understanding of the positive influences and mechanisms the arts have on health promotion. In particular, the current study draws on the influence of two psychological growth phases relted to creativity and ageing identified in older adults by Cohen (2009): the liberation phase, seen to emerge from one's mid-50s to mid-70s and the summing-up phase, frequently occurring in the late 60s and into the 80s.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies on music making have also highlighted its benefits for well-being. Group singing interventions have pointed to increases in general well-being (Clift et al, 2010), self-esteem, social bonding and meaning (Cohen et al, 2006; Davidson, 2011; Tarr, Launey, & Dunbar, 2014). With older adults, interventions focused on engaging with musical instruments have provided evidence towards anxiety reduction (Hars, Herrmann, Gold, Rizzoli, & Trombetti, 2014), a sense of accomplishment (Perkins & Williamon, 2014), purpose, control, autonomy, social well-being (Creech, Hallam, Varvarigou, McQueen, & Gaunt, 2013), and increased cognitive function (Seinfeld, Figueroa, Ortiz-Gil, & Sandrez-Vives, 2013).…”
Section: Introductionmentioning
confidence: 99%